Mechanistic insight of the formation of visible-light responsive nanosheet graphitic carbon nitride embedded polyacrylonitrile nanofibres for wastewater treatment. (February 2020) - Alias, Nur Hashimah; Jaafar, Juhana; Samitsu, Sadaki; Ismail, A.F.; Mohamed, Mohamad Azuwa; Othman, M.H.D.; Rahman, Mukhlis A.; Othman, Nur Hidayati; Nor, N.A.M.; Yusof, N.; Aziz, F.
Graphical abstract: Highlights: Synthesis of bulk and nanosheets g-C3 N4 from urea using facile template-free method. Fabrication of g-C3 N4 nanofibres via electrospinning technique. Photocatalytic degradation of MB by g-C3 N4 . MB capture by PAN nanofibres. MB purification by effective capture and in-situ photocatalytic degradation. Abstract: Effective capture and in situ photodegradation of methylene blue (MB) dye is a promising technique to purify wastewater containing MB. With recently elicited ripples of discovery on graphitic carbon nitride (g-C3 N4 ), this study investigates the performance of g-C3 N4 on photodegradation of MB. In this study, polyacrylonitrile (PAN) nanofibres embedded with g-C3 N4 photocatalyst was successfully prepared using electrospinning technique which produced liquid-permeable self-supporting photocatalytic nanofibre mats that can be handled easily. Different configurations of g-C3 N4 were synthesised, bulk g-C3 N4 (bg-C3 N4 ) and nanosheets g-C3 N4 (nsg-C3 N4 ) from urea using a green facile template-free method. Effective photocatalytic activity of the g-C3 N4 nanofibres was confirmed by 97.3% degradation of MB under visible light irradiation. Photodegradation of MB in aqueous solution by g-C3 N4 nanofibres predominantly attributed to the synergetic effects of MB adsorption by PAN nanofibres and photocatalytic degradation of MB by g-C3 N4 photocatalyst. This present work not only presents the simplest ecofriendly and economical approach to fabricate g-C3 N4 nanofibre photocatalyst, but also paves new opportunities for this advanced photocatalyst as great potential in environmental remediation for treatment of industrial MB wastewater.